2020
DOI: 10.7150/jca.37748
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-19a-3p regulates cell growth through modulation of the PIK3IP1-AKT pathway in hepatocellular carcinoma

Abstract: There are some controversies about the involvement of microRNA (miR)-19a-3p in hepatocellular carcinoma (HCC) biology, even though many studies have shown that it plays an important role in cancer. In this study, we found that miR-19a-3p is usually overexpressed in HCC tissues compared with corresponding peritumorous tissues, and its expression was associated with tumor size and poor overall survival. MiR-19a-3p promoted cell proliferation significantly, and more cells were found in the S phase. In vivo, miR-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Both miR-19a-3p and miR-19a-5p have been reported to be crucial in the promotion or inhibition of cancer progression. For example, miR-19a-3p was reported to promote the proliferation of hepatocellular carcinoma cells via regulation of the PIK3IP1/AKT pathway ( 30 ); however, another study reported that miR-19-3p induces colorectal cancer cell apoptosis by repressing the expression of Fas cell surface death receptor ( 31 ). Furthermore, miR-19a-5p expression is significantly decreased in NSCLC, and miR-19a-5p can suppress the proliferation, migration and invasion of NSCLC cells ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Both miR-19a-3p and miR-19a-5p have been reported to be crucial in the promotion or inhibition of cancer progression. For example, miR-19a-3p was reported to promote the proliferation of hepatocellular carcinoma cells via regulation of the PIK3IP1/AKT pathway ( 30 ); however, another study reported that miR-19-3p induces colorectal cancer cell apoptosis by repressing the expression of Fas cell surface death receptor ( 31 ). Furthermore, miR-19a-5p expression is significantly decreased in NSCLC, and miR-19a-5p can suppress the proliferation, migration and invasion of NSCLC cells ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to the previous publications, we have known that miRNAs drive the tumorigenesis of multiple cancers through regulating key genes expression. 20 Minichromosome maintenance genes exert a crucial role in DNA replication, including six genes MCM2-MCM7. 21 Liao et al analyzed distinct prognostic power and diagnostic value of MCM genes in HCC and found that MCM5 is significantly linked with the survival rate of HBV-induced HCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, 131 DEMs were identi ed, and of which four miRNAs such as miR-19a-3p, miR-144-3p, miR-223-5p, and miR-483-3p were associated with prognosis of PCa as the independent prognostic signatures in line with the Kaplan-Meier survival analysis, while the role of these DEMs in the progress of PCa is diverse depending on cancer types, which may act as oncogenes or tumor suppressors. MiR-19a-3p, as a key tumor-related miRNA of the miR-17-92 cluster (27), has been reported down-regulation in many types of cancers, including breast cancer (28), hepatocellular carcinoma (29), and glioma (30). MiR-19a-3p has been found high expression in primary PCa cell 22RV1, but was signi cantly decreased in bone metastatic PCa cell lines, including PC-3, C4-2B, and VCaP.…”
Section: Discussionmentioning
confidence: 99%